Analisis Implementasi Pendidikan Karakter Religius di Sekolah Dasar - Faradila Putri Tazkhiya; Fadhil Purnama Adi; Siti Istiyati Istiyati (Didaktika Dwija Indria, 2026)
Religious character education is a strategic effort in shaping a generation with noble morals, strong faith, and piety, as mandated by Law No. 20 of 2003 on the National Education System and Presidential Regulation No. 87 of 2017 on Character Education Strengthening. This study aims to: (1) describe the implementation of religious character education through habituation, exemplary behavior, and school activities at SD Negeri 1 Tempuran; (2) describe the roles of school members in implementing religious character education; and (3) identify the supporting and inhibiting factors that affect its successful implementation. This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, with purposive sampling as the sampling technique. Data validity was ensured through source and technique triangulation, while data analysis followed the interactive model of Miles and Huberman. The findings indicate that SD Negeri 1 Tempuran has implemented religious character education through daily habituation practices such as recitation of Asmaul Husna, congregational Dhuha prayers, and collective prayers before and after learning activities. The principal, teachers, and students each play complementary roles in the implementation process. Supporting factors include the commitment of school members and the availability of worship facilities. This study concludes that the implementation of religious character education at SD Negeri 1 Tempuran has been carried out consistently, yet still requires strengthened strategies in managing religious diversity in an inclusive and equitable manner.